Do police crackdowns disrupt drug cryptomarkets? A longitudinal analysis of the effects of Operation Onymous - Décary-Hétu, David (Crime, law and social change, 2017)
In recent years, there has been a proliferation of online illicit markets where participants can purchase and sell a wide range of goods and services such as drugs, hacking services, and stolen financial information. Second-generation markets, known as cryptomarkets, provide a pseudo-anonymous platform from which to operate and have attracted the attention of researchers, regulators, and law enforcement. This paper focuses on the impact of police crackdowns on cryptomarkets, and more particularly on the impact of Operation Onymous, a large-scale police operation in November 2014 that targeted many cryptomarkets. Our results demonstrate that cryptomarket participants adapt to police operations and that the impact of Operation Onymous was limited in time and scope. Of particular interest is the finding that prices did not increase following Operation Onymous, even though many dealers retired shortly after it occurred.